Integrasi Anggaran Responsif Gender dalam APBD (Studi pada Anggaran Dinas Pemberdayaan Perempuan dan Perlindungan Anak Provinsi Bali TA 2019) - Radha Dewi, Pande Try; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2020)
ABSTRACT The aimed of this research is to analyze integration of gender responsive budgets in the budgets at Women's Empowerment and Child Protection Office of Bali Province FY 2019. This research uses qualitative method and theory from Debbie Budlender with observation, interview and also documentation techniques of collecting data. The results of this research , first, budgets in Women's Empowerment and Child Protection Office of Bali Province is unresponsive, indicated that the integration of gender responsive budget rated only 44 . 28% of total direct expenditure budgets according to their percentage specific budget allocations were 9.45%, the budget allocation for equality gender only 6.72% and for mainstream gender were 28.1%. Gender unresponsive budgets or gender-neutral are 55.71% of total direct expenditure budgets. Seconds, integration of gender responsive budgets in the budgets got some constraints, namely policy, structural and cultural. Keywords: Gender, APBD and Gender responsive budgeting.